Explanation: We don`t know what is the number that is three times. So we will count it as 3x or any other variable along with 3. After that it is 5 subtracted from…. that means the 5 is being taken out of a number which here is 3x. So the equation formed is 3x-5. Now the difference is 6. So the final step which completes the equation is 3x-5=6

## Answers ( )

Answer: 3x-5= 6Explanation: We don`t know what is the number that is three times. So we will count it as 3x or any other variable along with 3. After that it is 5 subtracted from…. that means the 5 is being taken out of a number which here is 3x. So the equation formed is 3x-5. Now the difference is 6. So the final step which completes the equation is 3x-5=6

Answer:Step-by-step explanation:5-3n=6-3n=6-5

-3n=1

n=-1/3let’s check it heretake n=-1/35-3n=6

5-3(-1/3)=6

5+1=6

6=6

L.H.S=R.H.S